1997
DOI: 10.1007/pl00005132
|View full text |Cite
|
Sign up to set email alerts
|

The bovine thromboxane A2 receptor: molecular cloning, expression, and functional characterization

Abstract: This study describes the molecular cloning and functional characterization of the bovine thromboxane A2 (TP) receptor. Two partial nucleotide sequences coding for the bovine TP receptor were isolated from a bovine genomic and a bovine heart cDNA library. The deduced amino acid sequence suggests a heptahelical protein of 343 amino acids. The receptor protein is homologous with that of human placenta and endothelium at 84.0% and 81.4%, respectively. COS-7 cells were transfected with the bovine TP receptor cDNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Reverse transcriptase polymerase chain reaction (RT PCR) experiments indicated that HUVECs express only TPβ [32] whereas human platelets were reported to express both TPα and TPβ isoforms [33]. The physiologic significance for the existence of 2 receptors for TXA 2 in humans, but not in other species thus far investigated [21][22][23][24][25], is currently unknown but is an area of extensive research interest within my laboratory.…”
Section: Expression Of the Tp Isoformsmentioning
confidence: 98%
See 1 more Smart Citation
“…Reverse transcriptase polymerase chain reaction (RT PCR) experiments indicated that HUVECs express only TPβ [32] whereas human platelets were reported to express both TPα and TPβ isoforms [33]. The physiologic significance for the existence of 2 receptors for TXA 2 in humans, but not in other species thus far investigated [21][22][23][24][25], is currently unknown but is an area of extensive research interest within my laboratory.…”
Section: Expression Of the Tp Isoformsmentioning
confidence: 98%
“…A cDNA for the human TXA 2 receptor (TP) was originally cloned from placenta and the platelet like MEG-01 cell line [20] and since then cDNAs for TPs from a number of species have been cloned and characterised [21][22][23][24][25]. All TPs are predicted to share the seven α-helical transmembrane domain arrangement typical of other members of the GPCR superfamily [26].…”
Section: Expression Of the Tp Isoformsmentioning
confidence: 99%
“…Since the cloning of this receptor in 1991 by Hirata et al (79), homology screening based on its sequence was performed in various species, and all of the eight types and subtypes of the prostanoid receptors previously defined pharmacolgically were identified. They include the human and mouse PGD receptor (DP) (21,80); the mouse, rat, and human PGE receptor EP 1 subtype (22,63,244); the mouse and human PGE receptor EP 2 subtype (101,187); the mouse, human, rat, rabbit, and bovine PGE receptor EP 3 subtype (3,27,154,186,217,226,250); the mouse, human, and rat PGE receptor EP 4 subtype (originally reported as the EP 2 subtype; see below) (6,13,84,193); the mouse, human, bovine, rat, and sheep PGF receptor (FP) (2,70,110,191,216); the mouse, human, and rat PGI receptor (IP) (20,103,149,152,197); and the mouse, rat, and bovine TxA receptor (TP) (1,146,153). Initially, two species of cloned receptors were reported as EP 2 ; one was originally cloned by Honda et al (84) and subsequently by other people (6,13,193) and one was later cloned by Regan et al (187).…”
Section: A Prostanoid Receptors As Rhodopsin-type Receptorsmentioning
confidence: 99%
“…TxA 2 -TP receptor activity is coupled with G αs -, G αq -, G αi -, and G α12/13/15/16 -proteins (Shenker et al, 1991; Laugwitz et al, 1996; Muck et al, 1998). These G-proteins in turn regulate several effectors including phospholipase C, adenylyl cyclase, cAMP, guanine nucleotide exchange factor of the small G-protein Rho, and intracellular calcium (Kozasa et al, 1998).…”
Section: Prostaglandin Receptors (Ep3 Tp Dp2) Activating Both Camp mentioning
confidence: 99%